Efisiensi dan Produktivitas Kinerja Perguruan Tinggi Badan Layanan Umum Indonesia - Agus Sunarya Sulaeman; Sarah Sofi (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2022)
This study aims to evaluate the efficiency and productivity of 24 Public Universities as Public Service Agencies (PUPSA) in Indonesia. The approach used is a quantitative approach with the Data Envelopment Analysis and Malmquist Productivity Index methods. The findings in this study indicate that the average efficiency level of PUPSA in Indonesia is at an inefficient level. Only six (25%) PUPSA are able to maintain their efficiency during the study period and only three (12.5%) PUPSA do not experience changes in their efficiency scores due to changes in parameters. The malmquist productivity index approach finds that the average productivity of PUPSA increases, but it is dominated by technological improvements rather than technical efficiency improvements. In addition, quadrant analysis indicates that six PUPSA (25%) are in quadrant 1 (High Efficiency and Productivity), seven PUPSA (29.17%) are in quadrant 2 (High Efficiency, Low Productivity, six PUPSA (25%) ) are in quadrant 3 (Low Efficiency, High Productivity), and five PUPSA (20.83%) are in quadrant 4 (Low Efficiency and Productivity)